2022
DOI: 10.1097/aud.0000000000001263
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Aided Outcome With Aided Word Recognition Scores Measured With Linear Amplification at Above-conversational Levels

Abstract: Objectives: Many hearing aid (HA) users receive limited benefit from amplification, especially when trying to understand speech in noise, and they often report hearing-related residual activity limitations. Current HA fitting strategies are typically based on pure-tone hearing thresholds only, even though suprathreshold factors have been linked to aided outcomes. Furthermore, clinical measures of speech perception such as word recognition scores (WRSs) are performed without frequency-specific amplification, li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…The goal here is to provide sufficient amplification to normalize loudness at soft and conversational input levels and to reduce amplification for signal inputs above 75–80 dB SPL. This is partly motivated by the expected presence of ‘rollover’ in profile-C listeners, which can affect speech intelligibility at above-conversational levels [ 17 ]. To achieve this compression behavior, large compression ratios are required, which are not easily achievable with commercial HAs.…”
Section: Discussionmentioning
confidence: 99%
“…The goal here is to provide sufficient amplification to normalize loudness at soft and conversational input levels and to reduce amplification for signal inputs above 75–80 dB SPL. This is partly motivated by the expected presence of ‘rollover’ in profile-C listeners, which can affect speech intelligibility at above-conversational levels [ 17 ]. To achieve this compression behavior, large compression ratios are required, which are not easily achievable with commercial HAs.…”
Section: Discussionmentioning
confidence: 99%
“…Their own HAs were non-linear, multi-channel devices dispensed in 2017 and fitted according to standard clinical procedures. The participants were chosen based on results from an earlier study where they had shown statistically significant RO in their aided word recognition scores in quiet ( Fereczkowski & Neher, 2023a ). In the current study, they were tested on one side only.…”
Section: Methodsmentioning
confidence: 99%
“…While higher presentation levels typically lead to more audibility, they do not necessarily ensure maximum SI. Rather than plateauing out, SI can decrease with increasing presentation level (e.g., Fereczkowski & Neher, 2023a ; Studebaker et al, 1999 ). In the audiological literature, this phenomenon is termed “rollover” (RO; Jerger & Jerger, 1967 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations